Theoretical Study of the Nonlinear Control Algorithms with Continuous and Discrete-Time State Dependent Riccati Equation. (2016) - György, Katalin; Dávid, László; Kelemen, András
Abstract: The State-Dependent Riccati Equation (SDRE) control strategy is one of the most efficient approaches for the nonlinear feedback control algorithm by allowing nonlinearities in the system states. This method can be considered as a nonlinear LQR based control design, where the system matrices (and the weight matrices) are functions of the states. SDRE–based techniques have important properties which make them applicable for different nonlinear systems. In this paper we study some properties of these algorithms in order to improve the control efficiency and robustness of nonlinear process control. Also we compare the results of applied suboptimal and optimal SDRE control in continuous and discrete time case.